STABILITAS TOTAL FENOLIK, AKTIVITAS ANTIOKSIDAN, DAN AKTIVITAS PENGHAMBATAN α-GLUKOSIDASE PADA MINUMAN FUNGSIONAL BERBASIS SIRIH MERAH (Piper crocatum Ruiz & Pav.) - Syaefudin, Syaefudin; Safithri, Mega; Hasanah, Uswatun (Jurnal Gizi dan Pangan, 2016)
This study aims to determine the stability of total phenolic content, antioxidant activity, α-glucosidase inhibitory activity, physical properties (total dissolved solid, pH, color), and total microorganism of antidiabetic functional beverage at certain storage period. The functional beverage made from red betel leaf, cinnamon, and red ginger by using infuse method. Parameters were analyzed for 28 days on 10°C and 30°C of storage temperature. Antioxidant activity was measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, α-glucosidase inhibitory activity was determined in vitro, and total microorganism was measured by total plate count (TPC) method. The results showed that there were increasement in total dissolved solid of 1.92% (10°C) and 3.85% (30°C), and pH values of 15.30% (10°C) and 13.57% (30°C). In contrary, there were decreasement in total phenolic content of 61.63% (10°C) and 79.73% (30°C), antioxidant activity of 46.80% (10°C) and 53.19% (30°C), and α-glucosidase inhibitory activity of 5.43% (10°C) and 0.39% (30°C). Total microorganism at 10oC was <1.0×100 CFU/mL until day 28, while at 30oC was 2.0×100 CFU/mL on day 28. Based on the results, the functional beverage was good in physical and microbiological quality and still have biological activity as an antidiabetic beverage during storage.